2019
DOI: 10.1128/aac.00779-19
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Synergy of Ceftazidime-Avibactam in Combination with Meropenem, Amikacin, Aztreonam, Colistin, or Fosfomycin against Well-Characterized Multidrug-Resistant Klebsiella pneumoniae and Pseudomonas aeruginosa

Abstract: Multidrug-resistant (MDR) Gram-negative organisms are a major health concern due to lack of effective therapy. Emergence of resistance to newer agents like ceftazidime-avibactam (CZA) further magnifies the problem. In this context, combination therapy of CZA with other antimicrobials may have potential in treating these pathogens. Unfortunately, there are limited data regarding these combinations. Therefore, the objective of this study was to evaluate CZA in combination with amikacin (AMK), aztreonam (AZT), co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
98
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 126 publications
(114 citation statements)
references
References 29 publications
(10 reference statements)
6
98
1
1
Order By: Relevance
“…Colistin and tigecycline were largely indifferent in combination . Ceftazidime‐avibactam was not synergistic with fosfomycin against two isolates in one study but demonstrated synergy against three ceftazidime‐avibactam–resistant isolates in another study …”
Section: Fosfomycin In Combination With Other Antibiotics In In Vitromentioning
confidence: 97%
See 4 more Smart Citations
“…Colistin and tigecycline were largely indifferent in combination . Ceftazidime‐avibactam was not synergistic with fosfomycin against two isolates in one study but demonstrated synergy against three ceftazidime‐avibactam–resistant isolates in another study …”
Section: Fosfomycin In Combination With Other Antibiotics In In Vitromentioning
confidence: 97%
“…Several fosfomycin combinations have also been evaluated against K. pneumoniae . Colistin combinations have produced mixed results, demonstrating synergy against some isolates but showing indifference or antagonism against several others .…”
Section: Fosfomycin In Combination With Other Antibiotics In In Vitromentioning
confidence: 99%
See 3 more Smart Citations